Gaya Kepemimpinan dan Komitmen Paramedis dalam Implementasi Akreditasi Rumah Sakit Versi SNARS - Daniel Ginting; Nina Fentiana; Tiara Rajagukguk; Harry Wahyudi (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Clause 40 paragraph (1) of Law Number 44 of 2009 concerning Hospitals states that in an effort to improve the quality of hospital services, accreditation must be carried out periodically at least every three years. The leadership design is needed to support the formation of paramedic commitments in the implementation of accreditation. The research aims to identify the leadership style of direct paramedic leaders and paramedic commitment in the implementation of SNARS version accreditation. The study was designed with a cross sectional approach at Delia Hospital with a sample of 79 paramedics and using primary data obtained through observation and interviews. Correlation and simple linear regression tests showed leadership style and paramedic commitment in implementing hospital accreditation showed a strong and positive pattern of relationships. The results of the study concluded that achievement-oriented leadership style is the leadership style that is considered the most able to build paramedic commitment in the implementation of accreditation.